Incidence and Predictive Factors of Latent Tuberclosis Infection amongst Personnel of Ayatollah Rouhani Hospital in Babol, 2015-2016 - Bayani, Masomeh; Roushan, Mohammad Reza Hasanjani; Haji Li Doji, Abdolghayoum; Babazadeh, Arefeh; Ebrahimpour, Soheil; Javanian, Mostafa (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: The current study was designed to determine the incidence of latent TB and its predictive factors.METHODOLOGY: This was cross-sectional prospective study. Two tuberculin skin tests (TST) were performed in 400 health care staff (HCWs) of Ayatollah Rouhani Hospital Babol over one year and during the interview Age, Sex, Occupation, History of contact with tuberculosis and BCG scars were performed. Positive skin test was considered 10 mm; People with skin test less than 10 mm after one year were re-tested. An increase of more than 10 mm in the second test in negative PPD subjects was considered as a positive test. RESULTS: The prevalence of latent TB was 14.7% among the 400 health workers. 71.7% were women. The average age was 32.7 years. The incidence of latent tuberculosis was 6% (18 cases): technicians had the highest incidence (8.8%) and the nursing staff (6.6%), while services (2.5%) and administrative staff had the lowest incidence (0%). Out of these 18 people, 17 (94.4%) had reported a history of a patient with tuberculosis (TB) patient.CONCLUSION: According to the results of the study, the incidence of latent tuberculosis in this center is intermediate. The most important risk factor was the work experience of more than five years. Healthcare personnel training and infection control programs must be addressed adequately.